Penerapan Good Governance Dalam Peningkatan Kualitas Pelayanan Publik Di Masyarakat - Simbolon, Olan Mangondi; Manullang, Isabella Margaretha; Syahfitri, Nurul M; Tumanggor, Septri Jodi; Purba, Cindy Eliza; Saragih, Sonya Meilini; Ivanna, Julia (Mahesa Research Center, 2024)
This article or paper aims to describe how the implementation of good governance in improving the quality of public services in society. In addition, good governance in public services is needed because, without good governance, services will not run well. Public service is the provision of services to the community where services are provided according to the needs of each community. The problem is focused on how to improve Good Governance in public services, constraints in implementing public services, and the role of society and government in improving public services. To approach this problem, the method used is the library research method, in which data is collected through books, journals, the web, and others. The results show that there are obstacles faced in improving public services such as the large number of people who are not aware of the importance of licensing letters and the lack of notification to the public regarding services so people are confused.